2016
DOI: 10.1515/hukin-2015-0184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethnicity on the relationship between vertical jump and maximal power on a cycle ergometer

Abstract: The aim of this study was to verify the impact of ethnicity on the maximal power-vertical jump relationship. Thirty-one healthy males, sixteen Caucasian (age: 26.3 ± 3.5 years; body height: 179.1 ± 5.5 cm; body mass: 78.1 ± 9.8 kg) and fifteen Afro-Caribbean (age: 24.4 ±2.6 years; body height: 178.9 ± 5.5 cm; body mass: 77.1 ± 10.3 kg) completed three sessions during which vertical jump height and maximal power of lower limbs were measured. The results showed that the values of vertical jump height and maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is known that explosive power is related to the maximal speed and acceleration capability (Nordin et al, 2014;Peev, 2014;McFarland et al, 2016;Rouis et al, 2016). At the same time, a great number of sport professionals specify the quantitative values of explosive power as a method for control, selection and prediction of capabilities of the young players (Klavora, 2000;Markovic et al, 2004;Cunha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that explosive power is related to the maximal speed and acceleration capability (Nordin et al, 2014;Peev, 2014;McFarland et al, 2016;Rouis et al, 2016). At the same time, a great number of sport professionals specify the quantitative values of explosive power as a method for control, selection and prediction of capabilities of the young players (Klavora, 2000;Markovic et al, 2004;Cunha et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The CMJ test is common in physical education and sports training, as a means to assess lower limbs power and neuromuscular function. There was positive correlation between CMJ height with the knee extensor PT, individuals with higher lower limbs strength level have higher peak power when performing various jumping movements were reported by Uslu et al [35,36]. However, we failed to arrive at similar results, the parameters of CMJ have no difference in hikers and trapeze sailors, as well as high-level and low-level groups.…”
Section: Plos Onementioning
confidence: 41%
“…During the SSC the athlete commences a counter movement by first relaxing the agonist muscles, the quadriceps muscle is stretched eccentrically, which results in enhanced force production during the subsequent concentric phase [37]. Some studies have examined that the jump performance-isokinetic knee extensor muscles strength relationship depended on the angular velocity, with no or low correlation at slow angular velocities (lower than 180˚/s) and a moderate-high correlation at fast angular velocities [36]. Malliou and Ispirlidis stated that there was a significant correlation between the knee extensor PT at 60˚/s and CMJ height for professional soccer players after the completion of the competition and preparation period (r ranging 0.430-0.587) [38].…”
Section: Plos Onementioning
confidence: 99%
“…First, this study confirmed a strong relationship between jumping power and sprint cycling power in the current cohort of strength-trained ski cross racers. Whereas previous studies have shown similar relationships, usually using jump height rather than power, in untrained subjects [46], strength-trained non-cyclists [19,24,25,38,56], and strength-trained cyclist [27], this is one of few studies [45,47] to have directly compared mechanical power from both test forms. Thus, the close relationship between the two types of power measures seems to be fairly universal.…”
Section: Discussionmentioning
confidence: 90%
“…Although both cycling sprint and vertical jump tests are valid and well-established methods for assessing anaerobic power, they obviously differ considerably, particularly in their respective movement patterns (unilateral versus bilateral, and cyclic versus acyclic) and test durations (several seconds versus less than one second). Whereas several previous studies have addressed correlations between anaerobic cycling power and vertical jump height [19,24,25,38,45,46], the aforementioned evolution of methodology and consciousness make power-to-power the more obvious, and thus the more relevant comparison, today than was perhaps the case years ago. However, due to a surprising sparsity of published research on this topic [45,47], it remains unclear how well the power measurements from both tests-and more importantly with regards to performance testing, changes in these-correlate with one another.…”
Section: Introductionmentioning
confidence: 99%